Knights - Hanel, Rachael (Mankato, Minn. : Creative Education, 2008)
Describes the armor, weapons, and lives of medieval knights, and discusses famous knights and related legends.
Includes bibliographical references (p. 48) and index.
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
School Library Journal, January 2008.
Horn Book, April 2008.
Library Media Connection, February 2008.
Keywords: Knights and knighthood -- Juvenile literature; Civilization, Medieval -- Juvenile literature; Knights and knighthood; Civilization, Medieval; Knights and knighthood; Medieval civilization; Knights and knighthood; Civilization, Medieval